PRODUCTION ET ACCLIMATATION DE PLANTS DU GROS BASILIC (OCIMUM GRATISSIMUM) REGENERES IN VITRO : EFFET DE L’ACIDE NAPHTALENE ACETIQUE (ANA) SUR L’ENRACINEMENT - R., Dossoukpevi; S.J., Dangou; G., Cacaï; A., Agbidinoukoun; C., Agbangla; C., Ahanhanzo (European Scientific Journal, ESJ, 2015)
The present work aims to study the effect of Naphthalene Acetic Acid (NAA) on the rooting and acclimatization of Ocimum gratissimum plantlets. The cutting contain one knot (Explants) used are from the plantlets of first generation R0 of Ocimum gratissimum in the stage of multiplication and aged between 4 and 6 weeks. Explants (1cm) were inoculated on half Murashige and Skoog (MS/2) supplemented with 20g/L of sucrose and 7g/L of agar with different concentrations of Naphthalene Acetic Acid NAA (0; 0.5; 1 and 2mg/L) for root induction. After eight (8) weeks of culture, the rooting rate, the number of roots formed and the length of the primary root is determined by counting of roots by plantlets and the measuring of root length is made by a ruler. The experimental design was constituted of four tests with two repetitions. Each test includes 15 tubes represented treatments. The results showed that MS medium diluted to half and supplemented with 2mg/L NAA supports the root induction (4.70±0.5) while that with 1mg/L of NAA has produced the lowest average of roots (2.70±0.5). In acclimatization, 80% of rooted plants are able to survive. The conditions for successful rooting techniques in vitro under the effect of NAA (2mg/L) followed by the production of acclimated plants can be used for other research work on essential oils from plantlets of the specie studied.